An Office-Based Procedure for Hyphema Treatment - Mikelson MomPremier; Divya Sadhwani; Saad Shaikh (Case Reports in Ophthalmological Medicine)
Three cases of hyphema in three different eyes were treated in the office using an anterior chamber fluid-gas exchange technique. Hyphemas were associated with complications of underlying systemic and retinal disease and in the postoperative period of vitrectomy procedures. Patients were successfully treated without requiring return to operating room.